Nursing Students' Attitude toward the Importance of Patient Privacy - SeyyedHamidReza FallahMortezaNejad; Zahra Pourhabibi; Moein Mashayekhipirbazari; Kourosh Delpasand (Kashan University of Medical Sciences, 2021)
Background: Observing patient privacy is one of the most important nurses' ethical responsibilities. Objective: This study is aimed to investigate nursing students' attitudes toward the importance of patient privacy in nursing care. Methods: This cross-sectional study was conducted between September 2018 and April 2019 in the School of Nursing and Midwifery of Guilan University of Medical Sciences, Iran. One hundred and fifty nursing students responded to the study questionnaires. Descriptive statistics were used to analyze the data. Results: A total of 142 nursing students with a mean age of 21.91 ± 4.67 years participated in this study. A majority of the students (63.5%) were female, 82.2% were single and 31.8% had clinical experience. The mean students' attitudes scores were, respectively, 8.36 ± 1.53, 6.84 ± 2.04, 6.24 ± 2.23, and 11.42 ± 2.17 for the physical, psychological, spatial, and informational dimensions of patient privacy. Conclusion: The mean students' attitude toward patient privacy was at a moderate level. Nurse educators and all the authorities of nursing education should instruct nursing students to pay special attention to the observance of patient privacy.